Study of Coastal Community Health in North Maluku in the Utilization of TOGA - Liasari Armaijn; Nur Upik En Masrika; Amran Nur; Ismail Rahman; Muhammad Fakhrur Rajih; Abdul Hamid Siragih (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
Background: This study aims to examine the profile of Family Medicinal Plant (Tanaman Obat Kelaurga (TOGA) utilization among coastal communities on Hiri and Guaeria Islands as part of local wisdom-based health improvement efforts. Method: The study employed a mixed methods design involving 210 respondents. Quantitative data were obtained through questionnaires regarding knowledge, attitudes, and practices regarding TOGA utilization, while qualitative data were obtained through in-depth interviews and observations of medicinal plant processing and use practices in households. The results indicate that community knowledge of TOGA is in the fair category (53%), with an average score of 2.13. The community is generally familiar with several types of medicinal plants, such as ginger, turmeric, lemongrass, and betel leaf, for minor treatments. However, utilization practices remain limited, particularly in terms of sustainable processing and maintenance of medicinal plants. The main obstacles include limited land, knowledge of formulations, and lack of support from health workers. Conclusion: Overall, TOGA in coastal areas still has significant potential for development as part of a health promotion strategy and the resilience of traditional medicine communities. Community-based interventions are needed to increase community capacity in sustainable TOGA cultivation, processing, and utilization.